القدرات الاستراتيجية الإدارية ودورها في تحسين أداء العاملين - دراسة حالة: مديرية شركة مناجم الفوسفات ." تبسة Somiphos" - بوخاتم، لخضر (مجلة الإبداع, 2021)
هدفت هذه الدراسة إلى التعرف على مفهوم القدرات الاستراتيجية الإدارية كمفهوم حديث يلعب دورا محوريا في تحقيق النجاح والتفوق بالنسبة للمنظمات على الصعيد الداخلي والخارجي، من خلال التأثير في مختلف الأنشطة والمهام وخاصة أداء العاملين، الذي يعتبر بدوره من أبرز محددات تحقيق التفوق التنافسي للمنظمات، وتم اختيار مديرية شركة مناجم الفوسفات "Somiphos" تبسة لاختبار العلاقة على أرض الواقع بين القدرات الاستراتيجية الإدارية وأداء العاملين. وتوصلت الدراسة بعد جمع وتحليل مختلف البيانات إلى أن القدرات الاستراتيجية الإدارية وعبرها أبعادها الرئيسية والمتعلقة بالقدرات التنظيمية والقدرات التشغيلية تساهم بشكل كبير في تحسين من مستويات الأداء الفردية داخل مديرية شركة المناجم الفوسفات "Somiphos" تبسة.
Management Strategic Capabilities and Its Role in Improving the Performance of Employees - Case study: Directorate of Phosphate Mines Company "Somiphos", Tebessa.
This study aimed to identify the concept of strategic management capabilities as a modern concept that plays a strategic role in achieving success and excellence for organizations at the internal and external levels, By influencing various activities and tasks, especially the performance of employees, Which in turn is considered one of the most important determinants of achieving competitive excellence for organizations, The Directorate of Phosphate Mines Company "Somiphos" Tebessa was chosen to test the relationship on the ground between strategic management capabilities and employee performance. After collecting and analyzing various data, the study concluded that the strategic administrative capabilities, and through them, their main dimensions related to organizational and operational capabilities It contributes significantly to improving the individual performance levels within the Directorate of Phosphate Mining Company "Somiphos" Tebessa.